Role of CRP in Evaluating Acute Abdominal Pain: An Observational Study - Raheel Azhar, Raazia Ramzan, Saad Aslam, Jassim Jabbar, Madiha Karim, Ovais Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background:C-Reactive Protein (CRP) is an acute phase reactant that is routinely used in evaluation of cases with acute abdomen. We determined levels of CRP in patients with surgical causes that were either treated with operative or with non operative measures, and patients with non-specific abdominal pain. Objective: The aim of this study was to identify the use of C-reactive protein in differentiating between surgical causes of acute abdomen and non specific abdominal pain. Study Design:This is a prospective observational cohort study. Methodology: This study was conducted in General Surgery Department of Dow University Hospital, Ojha Campus, Karachi from January 2022 till October 2022. A total of 116 patients admitted with acute abdomen via Emergency were included in this study. Results: A total of 7 patients had non specific abdominal pain whereas the remaining 109 patients had surgical causes. 57 of those patients were managed conservatively while 52 underwent surgical interventions. Median value of CRP turned out to be 50, however CRP levels of the three groups had no significant impact on the evaluation of acute abdomen. Practical Implications: CRP levels are actively monitored in patients with acute abdomen. This study was conducted to find out if CRP levels can help assess the treatment of choice in such patients. The end result showed that CRP alone isn’t a helpful parameter to assess patients with acute abdomen. Conclusions: CRP is not a reliable marker in determining whether the patient has surgical abdominal pain or a non specific one. There is still room for further analysis to look for acute inflammatory markers that could help us evaluate the cause behind abdominal pain and guide us in devising a management strategy for the same. Keywords: CRP, C-reactive protein, Acute Abdomen, Non specific abdominal pain, operative intervention, non-operative intervention.